HUBUNGAN PENGETAHUAN DAN SIKLUS MENSTRUASI DENGAN ANEMIA PADA REMAJA PUTRI DI SMAN 13 KOTA JAMBI TAHUN 2026 - Dwi Haryanti; Elisa Ramadani; Nisa Kartika Ningsih; Silvia Mariana (LPPM STIKes Mitra Adiguna, 2026)
Anemia is a serious health problem worldwide, including in Indonesia. The most common type is iron deficiency anemia, a condition commonly experienced by adolescent girls and adult women (Pou et al., 2024). Factors that can cause anemia include inadequate knowledge about anemia, family income, infectious diseases, menstrual cycles, rest, and parental economic status. The purpose of this study was to determine the relationship between knowledge and menstrual cycles and anemia in adolescent girls at SMAN 13 in Jambi City. This research was quantitative with a correlation study. This research used a quantitative case-control approach, and data were collected by directly completing questionnaires. The sampling technique used total sampling. The population consisted of 32 adolescent girls and a sample size of 32 respondents. The statistical test used in the bivariate analysis was the chi-square test. The results of this study indicate that the majority of the 32 adolescent girls had good knowledge (53.1%) and a normal menstrual cycle (65.6%). Based on statistical tests using chi-square, a p-value of 0.038 was obtained for the knowledge variable and 0.010 for the menstrual cycle variable. Since both p-values are less than 0.05 (p<0.05), it can be concluded that there is a relationship between knowledge level and anemia, as well as between the menstrual cycle and anemia. The conclusion of this study is that there is a relationship between knowledge and anemia in adolescent girls at SMAN 13, Jambi City.